Meningkatkan Promosi Sekolah Berbasis Analisis SWOT Menghadapi Kompetisi di SMP Santa Maria Monica, Bekasi Timur - Putriyanti, Chatarina Catur; Fensi, Fabianus (Universitas Bunda Mulia, 2024)
This research aims to map the advantages of Santa Maria Monica Junior High School, East Bekasi, in order to promote the school using SWOT analysis. Mapping of advantages is used as a tool to promote schools in an era of increasingly fierce competition. Each educational institution must be able to offer something unique, which other educational institutions do not have. Santa Maria Monica Junior High School experienced something similar. The decline in the number of students registering is starting to be felt. This research tries to see what problems are causing the decline, even though this educational institution has many things that can be maximized to attract the interest of parents and students in choosing Santa Maria Monica Junior High School as the right place to study. By using a qualitative SWOT analysis method which focuses on strengths, weaknesses, opportunities and challenges to be faced, this research found that there are many things that Santa Maria Monica Junior High School can maximize to exist amidst the existing competition. It's just that promotion that is not optimal means that the public does not know what internal qualities the institution has so that parents' decisions to send their children to this education can be justified. Based on the strengths found and opportunities that can be exploited, this research also recommends several types of promotions that Santa Maria Monica Middle School can carry out to face existing competition, including: easily accessible location, comfortable school environment, adequate educational facilities, affordable education costs, qualifications of educational staff that meet standards, and recognition of excellence from the government. Existing internal advantages need to be promoted massively. This research recommends forms of promotion, apart from those currently carried out such as word of mouth (WOM) and relying on the school's status as a Catholic school, it is time to promote through social media (Facebook and Instagram) and hold educational exhibition events in surrounding elementary schools.